A Cyclic Alkyl(amino)carbene as Two‐Atom π‐Chromophore Leading to the First Phosphorescent Linear CuI Complexes. Issue 9 (18th January 2017) - Gernert, Markus; Müller, Ulrich; Haehnel, Martin; Pflaum, Jens; Steffen, Andreas
Abstract: The members of a series of linear and trigonal copper(I) complexes bearing a cyclic alkyl(amino)carbene (CAAC) ligand show surprising photophysical properties compared to those of the corresponding N‐heterocyclic carbene (NHC) complexes. Whereas the linear NHC complexes [CuX(NHC)] are almost non‐emissive, [CuX(CAAC)] (X=Cl, Br, I) and [Cu(CAAC)2 ]PF6 show very bright emissions from their triplet excited states in the blue to green region, displaying quantum yields of up to 65 % in the solid state, even though the π‐acceptor comprises only the carbene C and N atoms with no other π conjugation. [Cu(CAAC)2 ]PF6 is the fastest Cu I ‐based triplet state emitter characterized to date, not displaying thermally activated delayed fluorescence (TADF), with an intrinsic lifetime of only 10.6 μs, that is, k r =9.4×10 4  s −1, competitive with many Pt II ‐ and Ir III ‐based emitters. In order to test the stability of such linear copper CAAC complexes in devices, some of our compounds have been applied in proof‐of‐principle organic light‐emitting diodes (OLEDs). This case study thus demonstrates for the first time the use of CAACs as suitable π‐chromophores for Cu I ‐based phosphorescent emitters, and their implementation in OLEDs underlines the general applicability of this class of ligands in materials science. Abstract : Light up fast : A cyclic alkyl(amino)carbene has been shown to act as a π‐chromophore comprising only the carbene C and N atoms with no other π conjugation. By virtue of its superior σ‐donor and π‐acceptor properties compared to those of NHCs, it allows, for the first time, linear Cu I complexes to emit efficiently from their T1 states. [Cu(CAAC)2 ]PF6 is the fastest Cu I ‐based T1 emitter characterized to date, with a phosphorescence lifetime of only 10.6 μs (see graphic).